Measurement of D0, D+, D[star]+ and D+s production in Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Klewin, Sebastian; Knichel, Michael Linus; Leardini, Lucia; et al. (Journal of high energy physics, 2018)
We report measurements of the production of prompt D0, D+, D*+ and D s + mesons in Pb-Pb collisions at the centre-of-mass energy per nucleon-nucleon pair sNN−−−√=5.02sNN=5.02 \sqrt{s_{NN}}=5.02 TeV, in the centrality classes 0-10%, 30-50% and 60-80%. The D-meson production yields are measured at mid-rapidity (|y| < 0.5) as a function of transverse momentum (pT). The pT intervals covered in central collisions are: 1 < pT< 50 GeV/c for D0, 2 < pT< 50GeV/c for D+, 3 < pT< 50GeV/c for D*+, and 4 < pT< 16GeV/c for D s + mesons. The nuclear modification factors (RAA) for non-strange D mesons (D0, D+, D*+) show minimum values of about 0.2 for pT = 6-10 GeV/c in the most central collisions and are compatible within uncertainties with those measured at s√NN=2.76sNN=2.76 {\sqrt{s}}_{NN}=2.76 TeV. For D s + mesons, the values of RAA are larger than those of non-strange D mesons, but compatible within uncertainties. In central collisions the average RAA of non-strange D mesons is compatible with that of charged particles for pT> 8 GeV/c, while it is larger at lower pT. The nuclear modification factors for strange and non-strange D mesons are also compared to theoretical models with different implementations of in-medium energy loss. Open image in new window